PELAPORAN KINERJA INSTANSI PEMERINTAH (Studi Pada Kantor Kecamatan Rungkut Kota Surabaya) - Putri, Wulan Suci Ika; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to evaluate the presentation of Performance Accountability Reporting of Government Agency (LAKIP) and to assess the effectiveness and the efficiency of activity and program in order to evaluate the strategy planning. The object of the research is the government agency of Rungkut District Surabaya. The data collection technique has been done by conducting observation, interview, and documentation. The data analysis technique has been done by using qualitative descriptive. The analysis is done by collecting, processing, and presenting the obtained data so it can provide complete and valid information to solve the existing problems and to make other parties can have the description about the characteristic of the object of the data. A study is needed on the performance indicator assessment i.e. input indicator, output indicator, and outcome, and the characteristic of the outcome. The 2014 Performance Accountability Reporting of Government Agency (LAKIP) and other related data is used to support the research. The manifestation of the performance accountability of Rungkut District Surabaya is generated from the developed performance assessment system which can be used to assess the efficiency and the effectiveness of the implementation of program and activity. Nevertheless, efforts are needed to develop the relevant performance measurements with the implementation of activity and program.Keywords: Performance Reporting, Accountability, Efficiency, Effectiveness.